Man arrives : the story of human evolution - Hyndman, Michael (London : George Allen & Unwin, 1974)
An up-to-date view of the search for man's ancestors and the present theories of human evolution. (Bron: covertekst)
Keywords: 062909jpg; Prehistorie; Evolutieleer ; mensen